The Initiatives of Green Supply Chain Management (GSCM) in the Malaysian Construction Industry - Nur Syamimi, Zulkefli; Mohd Ridzuan, Darun; Nurhaizan, Mohd Zainudin; Zarith Sufia, Azlan (2014)
Nowadays, green supply chain management (GSCM)has gained greater attention to the construction industry players because of the concern of the people on environmental and sustainability issues. Thus, this study is being conducted with the aims to identify the green supply chain initiatives in the Malaysian construction industry. Aside from literature review, semi-structured interview were conducted to two project’s team in order to gain insight review on the initiatives implemented by each of the party during the construction supply chain phase. The study suggests that the level of adoption of GSCM in the Malaysian construction industry was still at the development phase. The initiatives of GSCM implemented was not as a whole and restricted to several supply chain phase only mainly green design, green purchasing and green construction. It is hoped that, the study information will be useful in promoting GSCM amongst the Malaysian construction industry players.